A survey on Agriculture Using Internet of Things - Keerthiga, D; Ganesan, M (International Journal of Computer Sciences and Engineering, 2025)
The internet of thing is a system of physical articles that can ready to gather and trade information utilizing installed sensors. The reason for this is to plan and build up a horticultural field checking framework utilizing Internet of things to expand the efficiency and nature of cultivating without watching it for all the time physically. IoT is quick developing innovation that helps in gathering data about conditions like humidity, temperature, moisture, and soil fertility, level of water, rain sensor, animal detection and agriculture. IoT innovation encourages agriculturists to get joined to his homestead from anyplace and whenever. The farm conditions are monitored by wireless sensors and micro controllers are used to control and automate the farm processes. IoT enables the farmers to view farm conditions remotely in the form of images. The ongoing condition of agricultural land is keep updated to farmers through smart phone using IoT at any time and any part of the world. It can also reduce the cost and enhance the productivity of traditional farming